Urachal cyst and enteric duplication in a pediatric patient - Allen K. Chen; Michael J. Allshouse (Elsevier, 2019)
Here we present an unusual case of a 3-year-old male with multiple congenital developmental abnormalities discovered during laparotomy: an urachal cyst and enteric duplication. This combination of anomalies has not been described before. Keywords: Urachal cyst, Enteric duplication